Assessing the environmental impact of Kolaka peridotites from nickel mining waste for geological carbon storage: Mineralogy, carbonation potential, and rock property changes - Deniyatno, Deniyatno; Masri, Masri; Jaya, Rio Irhan Mais Cendra; Wahab, Wahab; Syahrul, Syahrul (Journal of Degraded and Mining Lands Management, 2025)
This study investigated the carbonation potential of peridotite from the Kolaka Ultramafic Complex in Sulawesi, Indonesia, for carbon capture and storage (CCS) applications. Peridotites, particularly those enriched in magnesium, are known for their high reactivity with CO?, forming stable mineral carbonates. However, the Kolaka region’s peridotites have not been thoroughly assessed for their carbonation prospects. This research addresses this gap by examining the petrology, geochemistry, and physical-magnetic properties of peridotite, focusing on its serpentinization and carbonation characteristics. An integrated approach applying petrographic analysis, X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), Schmidt hammer, and magnetic susceptibility tests, was used to determine the mineral composition, specifically the carbonation minerals, and the changes in the physical properties of the rocks during carbonation. The results showed that the peridotites, particularly serpentinized lherzolites, exhibit high carbonation potential characterized by the abundance of magnesium-rich olivine-pyroxene minerals. Carbonation reactions are characterized by the presence of magnesite and brucite, leading to significant changes in rock strength and magnetic susceptibility. Carbonation occurs by an advanced serpentinization process, which increased mineral reactivity and leads to reducing uniaxial compressive strength (UCS). Additionally, magnetic susceptibility exhibits positive correlation with serpentinization, accompanied by magnetite formation. These findings suggest that Kolaka's serpentinized peridotite, as mining waste, is a viable candidate for CO? storage. The ex-situ carbonation mechanism allows Kolaka's fine-grained peridotite to capture CO?, while also improving nickel ore recovery, minimizing dust, neutralizing acid mine drainage, and enhancing soil quality.